2012
DOI: 10.2134/agronj2011.0416
|View full text |Cite
|
Sign up to set email alerts
|

Net Return Risk for Malting Barley Production in Western Canada as Influenced by Production Strategies

Abstract: Th e objective of this study was to evaluate the impact of agronomic practices on net return (NR) risk for malting barley (Hordeum vulgare L.) production. Th is study used data from two fi eld experiments conducted from 2005 to 2008 at eight rainfed locations in western Canada. Th e fi rst part of this study included 30 production strategies of barley type, seeding rate, and N rate for four regions. Th e second part of this study included 10 production strategies of seeding date and seeding rate for four regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
1
8
3
Order By: Relevance
“…The average applied N rate in this study with a previous crop of barley was 61 kg N ha −1 , and the 50% rate was about 30 kg ha −1 . The 100% rate of 60 kg N ha −1 applied to barley was consistent with that reported by Smith et al (2012) and Khakbazan et al (2014) for maximum return. This study though found no difference in net return between the 100% rate and the 50% rate (30 kg N ha −1 ).…”
Section: Resultssupporting
confidence: 87%
“…The average applied N rate in this study with a previous crop of barley was 61 kg N ha −1 , and the 50% rate was about 30 kg ha −1 . The 100% rate of 60 kg N ha −1 applied to barley was consistent with that reported by Smith et al (2012) and Khakbazan et al (2014) for maximum return. This study though found no difference in net return between the 100% rate and the 50% rate (30 kg N ha −1 ).…”
Section: Resultssupporting
confidence: 87%
“…1. Grain yield and yield response to N: Compared to our results, lower yields and maximum N responses were observed by Kassie and Tesfaye (2019b), Smith et al (2012), andMcKenzie et al (2004) (i.e., maximum GY of ∼5,500 kg ha −1 and maximum N response of ∼1,400 kg ha −1 , respectively). Greater EONR is expected with increases in yield and N responses due to improvements in the growing conditions (i.e., high-yielding environments, Prystupa et al, 2018) and/or high-yielding cultivars (McKenzie et al, 2004).…”
Section: Sitecontrasting
confidence: 97%
“…Pendell et al (2007) considered the effectiveness of soil C sequestration strategies under alternative N and tillage management practices by ranking the strategies using SERF analysis. Smith et al (2012) demonstrated the ability of SERF analysis to effectively rank large numbers of alternative practices by analyzing 40 barley ( Hordeum vulgare L.) production strategies in western Canada, ranked by risk preference. Using published experimental data from across the United States, Toliver et al (2012) evaluated differences in downside yield risk associated with tilled and no‐till management practices for sorghum [ Sorghum bicolor (L.) Moench], soybean, oat ( Avena sativa L.), cotton, and wheat.…”
mentioning
confidence: 99%